2015
DOI: 10.1007/s12263-015-0469-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of metabolic health effects of the flavonoids quercetin, hesperetin, epicatechin, apigenin and anthocyanins in high-fat-diet-fed mice

Abstract: Dietary flavonoid intake is associated with reduced risk of cardiovascular diseases, possibly by affecting metabolic health. The relative potency of different flavonoids in causing beneficial effects on energy and lipid metabolism has not been investigated. Effects of quercetin, hesperetin, epicatechin, apigenin and anthocyanins in mice fed a high-fat diet (HF) for 12 weeks were compared, relative to normal-fat diet. HF-induced body weight gain was significantly lowered by all flavonoids (17–29 %), but most by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 33 publications
3
54
0
1
Order By: Relevance
“…Although the body weight gain was lower in the EC supplemented HFD mice, this reduction per se seems improbable to account for the observed major improvement of systemic insulin sensitivity. In mice fed a HFD similar to that the used in our current study, but receiving 16 times higher EC, the decrease in body weight gain was partial and of similar magnitude [29]. This suggests that at 20 mg/kg body weight/d, dietary EC may have already reached the maximum potential benefit on HFD-induced mouse body weight gain, and that higher EC consumption may have limited benefits.…”
Section: Discussionmentioning
confidence: 53%
“…Although the body weight gain was lower in the EC supplemented HFD mice, this reduction per se seems improbable to account for the observed major improvement of systemic insulin sensitivity. In mice fed a HFD similar to that the used in our current study, but receiving 16 times higher EC, the decrease in body weight gain was partial and of similar magnitude [29]. This suggests that at 20 mg/kg body weight/d, dietary EC may have already reached the maximum potential benefit on HFD-induced mouse body weight gain, and that higher EC consumption may have limited benefits.…”
Section: Discussionmentioning
confidence: 53%
“…One persistently up-regulated gene, Cyp2b9, displays the most dramatic increase in response to HF diet. This gene encodes for a cytochrome P450, which previously has been shown to be strongly up-regulated by HF diet and important for regulating lipid homeostasis (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has shown that psychological stress may correlate with the increasing incidence of metabolic syndrome, inflammation, and NAFLD [41, 42]. However, previous studies mostly concentrated on the effect of chronic stress on obesity or metabolic syndrome combined with a high-fat diet [43, 44].…”
Section: Discussionmentioning
confidence: 99%